Does not quantum compute. - Guizzo, E. (IEEE spectrum)
D-WAVE systems, a Canadian start-up, recently booted up a custom-built, multimillion-dollar, liquid-helium-cooled beast of a computer that it says runs on quantum mechanics. That's right. D-Wave, a 55-person company operating out of an office park in Burnaby, B.C., claims to have built that almost mythical machine, that holy grail of computing, the stuff of sci-fi novels and technothrillers - the quantum computer. Such a system would exploit the bizarre physics that apply on ridiculously small scales to compute ridiculously fast, solving problems that could stymie today's supercomputers for the lifetime of the universe.